Klarifikasi Tentang Pendapat James Bellamy Mengenai Kritik Terhadap Teks Al-Qur’an - Komaru Zaman (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2021)
Studying and understanding the Qur'an which is a sacred text for its adherents is the basic thing needed so that in carrying out daily activities it can be in accordance with the teachings in it. However, it is undeniable that the text if examined in the eyes of the world of academia and research is only based on a scientific point of view, it can have both positive and negative impacts. As an opinion emerged from James Bellamy who tried to criticize the text of the Qur'an. With this, it can cause a problem, namely what text is the object of research, then how is the method used in criticizing the text of the Qur'an. So in this article, we will describe the text that became the research as well as the method in criticizing the text of the Qur'an. In short, there are several things that can be conveyed that Bellamy's criticism is more dominated by criticism of lafadz or verses of the Qur'an by trying to change and shift the lafadz according to what he understands, not believing in the validity of the Uthma>ni mush{af that have been written. codified since the time of Uthman's companions.